Collections of the wild Daucus carota L. preserved at VIR - L. Yu. Shipilina; T. V. Khmelinskaya (Труды по прикладной ботанике, генетике и селекции, 2024)
Carrot is a crop cultivated worldwide. That is why a study of the Daucus carota L. diversity maintained at VIR is of interest, since it helps to assess its potential for breeding practice and genetic research. Presently, carrot is represented in the VIR collection by 3,227 accessions, 236 of which are wild carrots from 33 countries. Morphological characters of 183 wild carrot accessions were studied for seven years (2016–2022), and taxonomic affiliations were ascertained for 106 of them. The material was delivered from Eurasian and African countries.The VIR herbarium (WIR) contains carrot specimens brought by collecting missions from various countries. In total, the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) launched 66 collecting missions whose objectives included wild carrots as one of the priorities. Those expeditions explored the territories of Russia, Europe, Asia, America, and Africa. The herbarium now contains 323 carrot specimens, with 249 belonging to the wild D. carota species. Intraspecific taxa of D. carota are represented. The herbarium of cultivated carrots consists of 74 specimens.The studied 106 wild carrot accessions from the VIR collection were identified, herbarized, arranged, incorporated into the WIR database, and placed into the permanent herbarium collection. As a result of this work, the WIR herbarium now contains 351 wild D. carota specimens, while the collection of cultivated carrots has been replenished with 4 accessions requiring verification.